Avaliação da variabilidade de qualidade ambiental de bacias de mananciais de abastecimento público com a aplicação de um índice para o estado de Goiás - Cruvinel, Karla Alcione da Silva (2016)
The need for environmental preservation and responsible use of natural resources is something increasingly discussed between civil society and the scientific community and the need to monitor the environmental quality of areas such as river basins requires planning and choice of variables that help in understanding functionality of these systems. In addition, the index and indicators are presented as efficient tools in order to make them more easily visualized technical data. In this study, socioeconomic and environmental indicators were used in order to structure an index able to estimate the degree of environmental quality of the watershed. The Environmental basins Quality Index (EQI) was built from the variables Soil Loss (SL), Native Vegetation Index (NVI), Water Quality Index (WQI) and Municipal Development Index (MDI). The GIS was used to identify the NVI and loss of soil in the basin, and for the latter employed Universal Soil Loss Equation (USLE). It was applied still Soil and Water Assessment Tool software (SWAT) in soil loss prediction five basins studied in order to promote the direct comparison of the model front applicability of the method implemented USLE. We studied different scenarios in these same five basins in SWAT, which we sought to evaluate the influence of vegetation in sediment yield for different land cover scenarios. To obtain the WQI of each basin, we used the adaptation of the method developed by Sousa (2014). After that, the EQI was applied in 126 basins of supply water sources in Goias State, which enabled the identification of the degree of environmental quality of each. It was found that almost 85% of the studied basins are classified as very bad or bad EQI, and in almost all of these the WQI of the spring is also bad. By analyzing the EQI basins in ten different regions of Goias State Planning it was noted that average is best in the Northwest region, which also has better native state of vegetation index. Regarding the loss of soil, it is noted that most of the basins (64%) are classified in low and moderate erosive susceptibility, but with some in erosive susceptibility very high severe. Therefore, it was concluded that the methodology used in this study proved to be an effective management strategy for catchments and can be used as an environmental planning instrument in these areas.